LARGE EMPHYSEMATOUS BULLAE MIMICKING AS A PNEUMOTHORAX LEADING TO UNNECESSARY CHEST TUBE INSERTION AND IATROGENIC PNEUMOTHORAX - Khan, Qalb; Batool, Anisa; Haider, Muhammad Adnan; Hanif, Muhammad; Ali, Mukarram Jamat; Sattar, Saud Bin Abdul; Khan, Sheraz Jamal (Journal of Ayub Medical College Abbottabad, 2021)
Pneumothorax (Pnx) is the presence of air or gas in the pleural space which hinders the lungs to function appropriately. Pneumothorax that presents in the absence of any underlying aetiology is called primary spontaneous pneumothorax (PSP) and on the other hand, it may present as a complication of underlying lung disease which is known as secondary spontaneous pneumothorax (SSP). Iatrogenic Pneumothorax (IP) is a type of SSP and is caused by medical interventional procedures which include transthoracic needle biopsy (24%), sub clavicular catheterization (22%), thoracocentesis (20%), transbronchial biopsy (10%), pleural biopsy (8%) and positive pressure ventilation (7%). We had a 51-year-old patient with a history of COPD/emphysema who presented with respiratory distress. Large bullae were mistaken as pneumothorax, unnecessary Chest Tube Insertion (thoracostomy) was performed resulting in IP. An extensive review of the literature shows there are only a few reported cases of unnecessary thoracotomy and IP in settings of giant bulla mimicking pneumothorax. Iatrogenic Pneumothorax resulting from giant bullae mimicking pneumothorax leading to unnecessary chest tube insertion. Physicians should be aware of such aetiology of pneumothorax as it has been rarely reported in the literature.